Blend Films of Waterborne Polyurethane-Carboxymethylated Guar Gum Crosslinked by Ca2+ - Huang*, Aibin; Le, Wanwan (Asian Journal of Chemistry, 2014)
Films from waterborne polyurethane (WPU) and carboxymethylated guar gum (CMGG) with different contents (20-80 wt %) were prepared through solution casting method and then were crosslinked with calcium chloride. The effect of CMGG content on the miscibility, morphology and physical properties of the blend films is investigated by Fourier transform infrared spectroscopy, scanning electron microscopy, density measurements, differential scanning calorimetry, dynamic mechanical thermal analysis, thermogravimetric analysis, water sensitivity measurements, solvent-swelling and tensile tests. The results reveal that the uncrosslinking films exhibit good miscibility when CMGG content is lower than 60 wt %, whereas typical “sea-island” structure occurs when the CMGG content further increases. After crosslinking with calcium ion, the blend films form a relatively dense architecture, which leads to better miscibility, higher storage modulus and thermal stability. The crosslinking films also exhibit better tensile strength (11.6-56.5 MPa) and solvent-resistance than that of the uncrosslinking films over the entire composition range. A model describing the configuration of Ca2+-chelating structure was proposed to illustrate the different structures of the two series of the blend films.